1997
DOI: 10.1093/molehr/3.10.853
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of P[gal4] insertion lines of Drosophila melanogaster as a route to identifying genes important in the follicle cells during oogenesis

Abstract: We report the analysis of a number of lines of Drosophila melanogaster containing insertions of the yeast gal4 gene. By crossing a UAS-lacZ fusion gene as a reporter into these lines, we analysed the expression patterns of beta-galactosidase during oogenesis. Since there is no expression of GAL4 in the germ-line in these experiments, this is an ideal system for the analysis of expression patterns in sub-sets of follicle cells. These lines provide ideal markers for sets of follicle cells, e.g. anterior or poste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The follicle cells in turn are involved in specifying the dorsal-ventral axis of the subsequent egg. While we were searching for genes downstream of the Grk/EGFR signalling pathway expressed in follicle cells, using a GAL4/UAS enhancer trap system (Deng, et al, 1997), we cloned the bves gene. A developmental Northern analysis showed that bves is expressed in oogenesis, embryogenesis and postembryogenesis (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The follicle cells in turn are involved in specifying the dorsal-ventral axis of the subsequent egg. While we were searching for genes downstream of the Grk/EGFR signalling pathway expressed in follicle cells, using a GAL4/UAS enhancer trap system (Deng, et al, 1997), we cloned the bves gene. A developmental Northern analysis showed that bves is expressed in oogenesis, embryogenesis and postembryogenesis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For other lines refer to papers referenced. grk HK and grk WG (Schüpbach, 1987), fs(1)K10 (Wieschaus et al, 1978), UAS-lacZ (Brand and Perrimon, 1993), GAL4 line C648 (Deng et al, 1997). All flies were raised on standard cornmeal-yeast agar medium at 25ºC.…”
Section: Fly Stocksmentioning
confidence: 99%
“…The stocks used in these experiments are: C865 (Deng et al, 1997); jar mmw14 (Hicks et al, 1999); y 1 w -; TM3, Sb 1 /TM6B, Tb þ ; w-; P[D2-3]Dr/w-, TM6, Tb; Ly 1 / TM6B, P{w þmW.hs ¼ UbiGFP.S65T} PAD2, Tb 1 ; Df(3R)crb87-5, st 1 e 1 /TM3, Ser 1 , (Bloomington Stock Center), UAS-DATPjar (Pertrisch et al, 2003), engrailedgal4 (Brand A) e22c .…”
Section: Generation Of Jar Mutants and Fly Crossesmentioning
confidence: 99%
“…The deletion chromosome, Df(3R)S87-5, was made by Elizabeth Knust and Jose Campos-Ortega and others (University of Koln) and was obtained from Eric Weischaus (Princeton University). The starting P insert line, C865, came from a Gal4 screen for genes expressed in a subset of follicle cells in oogenesis (Deng et al, 1997(Deng et al, , 1999.…”
Section: Fly Culturementioning
confidence: 99%